Readiness, challenges and motivation for certification among halal restaurants in Northeastern Thailand - Wannasupchue, Wannasiri (2020)
In 2018, 38.3 million international tourists arrived in Thailand. The tourism industry generated USD54 billion of revenue for the country. Besides, the number of tourist arrival is expected to increase by 10 percent annually, which lead to the revenue increase in the food and beverage sector. This sector was identified as one of the top five sectors that contributed 12.3% to the national gross domestic product (GDP) in 2018. The northeastern area in Thailand is becoming popular among Muslim travelers and there is a high demand for halal food. There were 19,615 of Muslim tourists who chose this region as their travel destination in 2017. Nevertheless, there were only 11 halal certified restaurants to accommodate the influx of Muslim tourists in that area. Halal food is not only intended for Muslim customers; it is also preferred by non-Muslims. Thus, it is critical to promote halal certification among restaurant owners in northeastern Thailand. The main objective of this study was to explore the readiness, challenges and motivation for certification among halal restaurants in the northeastern Thailand. Semi-structured interviews and observation were conducted with informants comprising three stakeholders: restaurant operators of halal certified restaurants (HCRs) and non-certified halal restaurants (NCHRs), halal authority, and customers. The data was analyzed using thematic analysis with computer software (ATLAS.ti. 8.4). Six themes emerged as the readiness dimensions, in answering the first objective: appropriateness, management support, effort, restriction, personal benefit and restaurant benefit. This study also mapped the restaurants into six readiness stages, where NCHRs were identified at the pre-contemplation and contemplation stages, and HCRs were at the maintenance and termination stages. The second research objective revealed seven themes of the motivation factors and four themes of benefits in having halal certification. In the third objective, there were six themes of motivation factors perceived by customers in choosing halal restaurants. The challenges of having halal certification were obtained from three different perspectives; HCRs, NCHRs and halal authority. Three categories of challenges emerged from the fourth objective: namely before, in applying, and after getting halal certification. The final objective of this study identified that the halal authority implemented halal training and provided hard copy documents in the past. Currently, all the halal related documents can be downloaded and submitted online. In the future, the authority strategized to develop applications to facilitate the halal activities. The findings of this study are anticipated to give insights on how restaurant owners should strategize their business towards acquiring a halal certification, help to better understand the current situations and efforts that should be carried out by the authorized bodies for halal certification in Thailand. In addition, the readiness themes and the definition of the readiness stages developed by this study can be applied to the halal restaurants in other regions, particularly in Thailand.